Angiotensin converting enzyme inhibitor and coenzyme Q10 as adjunctive treatment for patients with ventricular septal rupture following late onset myocardial infarction: a case report - Ryan Enast Intan; Dimas Rio Balti; Ricardo Adrlan Nugraha; Firas Farisi Alkaff; Sovia Salamah; Tan Nicko Octora (Journal of the Pakistan Medical Association, 2024)
Ventricular Septal Rupture (VSR) is a rare complication of acute myocardial infarction and has a high mortality rate. Surgery is the definitive treatment. However, in hospitals with limited facilities, treating acute myocardial infarction patients with ventricular septal rupture, is challenging. A 74-year-old woman came to the emergency room of Dr. Koesma General Hospital, Tuban, East Java in December, 2019 with late-onset Acute Myocardial Infarction. On the following day, a new holosystolic murmur was heard in the left lower sternal border with palpable thrill. Transthoracic echocardiography showed VSR with severe pulmonary hypertension. This was followed by a drop in the blood pressure to 80/50 mmHg. The blood pressure was dependent on vasopressors until lisinopril and coenzyme Q10 were introduced. After 3 months, the haemodynamics of the patient were stable. This proved that the use of angiotensin-converting enzyme and coenzyme Q10 promotes more energy production, enables tissue healing and leads to balanced remodelling to increase the survival rate in cases of non-surgical treatment. Keywords: Lisinopril, Ventricular Septal Rupture, Heart Murmurs, Vasoconstrictor, Hemodynamics, Angiotensin’s, Infarction, Coenzymes